Implementation Of Marketing Strategies Using A Swot Analysis Approach To Increase Sales at Pt. Digital Tries Indonesia - Gibran Safira Darumawan; Anas Hidayat (International Journal of Business and Quality Research, 2024)
Caused by the rapid development of technology, business competition in the current era of globalization is increasingly fierce and complex. Companies must consider both internal and external factors that affect them, and SWOT analysis is an important tool for doing so. This analysis allows companies to know their internal strengths and weaknesses, as well as external opportunities and threats, so that they can take appropriate strategic actions to stay competitive in the market. This research aims to see whether PT Tries Digital Indonesia's marketing strategy can increase sales by using SWOT analysis, which evaluates the company's strengths, weaknesses, opportunities, and threats. This research was conducted qualitatively and the data mainly came from observations or interviews. The results showed that PT Tries Digital Indonesia has strengths in terms of quality IT products and services, but faces challenges due to wider market penetration and increasingly fierce competition. To increase sales, the company must take advantage of market opportunities, improve internal weaknesses, and overcome external threats. It is hoped that this research will help PT Tries Digital Indonesia create an effective marketing strategy to increase sales..